PENGARUH TERPAAN BEAUTY VLOG DI YOUTUBE DAN TINGKAT PENGETAHUAN BAHAYA MAKE UP TERHADAP PERILAKU PENGGUNAAN MAKE UP PADA ANAK - Mayangsari Cantika Mutiara; Lintang Ratri Rahmiaji (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This research is motivated by the rise of the phenomenon of using makeup in children eventhough make up has a negative impact when used too early. Make up can have a negative impacton the physical, psychological, and even social life of the child. The closeness of children to theinternet makes it easy to access Youtube specifically accessing those who currently floodYoutube content, make up tutorial videos. This study aims to determine whether there is aninfluence of exposure to beauty vlogs and the level of knowledge of danger of make-up on theuse of make-up behavior in children.This research is a quantitative research with an explanatory type of research that causes causationbetween variables. The research took the subject of research of children who watched Youtubeand had watched beauty vlogs that were sitting in elementary schools in the city of Semarang.The study uses Multiple Linear Regression Analysis.The results of the study show that the exposure variables of Beauty Vlog on Youtube and theLevel of Knowledge of Danger of Make Up on the Behavior of Make Up on Children have acalculated F value <F table which is 2.053 <3.09 which means the hypothesis Make Up has aneffect on the Behavior of Using Make Up on Children